APPROACHES TO ASSESSING THE EFFECTIVENESS AND WAYS TO ENCOURAGE THE PUBLICATION ACTIVITY IN THE LARGE MEDICAL SCHOOL - Vladimir N. Nikolenko; Anatoliy I. Vyalkov; Svetlana A. Martynchik; Ekaterina A. Glukhova (Высшее образование в России)
The article deals with the topical problem associated with the evaluation methodology of publication activity and ways to stimulate the publication activity in a large medical school. There is investigated the development of theregulatory framework in relation to the structural modernization of the public sector science. We apply anintegrated approach to performance evaluation based on expert evaluation of the importance of research and bibliometric analysis in the citation index. The article presents the structure and functionality of the publication activity indicators. A list of criteria for effectiveness of the medical school as a part of the «road map» is given. Methods of improving the publication activity and ways for its promotion at author’ and organization level are presented. The key factors forsuccessfulness of organizational and administrative measures to improve the publication activity and university rankings are computer support of R&D and scientific communication, acquisition of new above professional and inter-professional skills and competences by researchers, implementation of effective analytical online resources, monitoring of research activities, special seminars for training researchers to operate online resources.